STUDI FENOMOENOLOGI: PENGALAMAN PENDERITA GANGGUAN MUSKULOSKELETAL YANG MENJALANI TERAPI YOGA - Hardiah Utari; Wasisto Utomo; Wan Nisfha Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Musculoskeletal disorders are disorder occur in bones, joints, muscles, ligaments, tendons and connective tissues. The disturbance occurs in the musculoskeletal system was characterized by pain that decrease the physical ability. Patients with chronic musculoskeletal disorder prefer to treat their pain with complementary therapies, one of that is yoga. This study aims to explore the experiences of patients with musculoskeletal disorder who undergo yoga at Shena Studio. This study used qualitative method with phenomenological approach. The result of this study were obtained after in depth interviews with 3 participants who have different type of musculoskeletal disorders. They were suffering from scoliosis, low back pain with osteoarthritis, and osteoarthritis with osteoporosis. The interview result has been analyzed using Collaizi method. The result of study include 4 themes (1) feelings and experience during yoga (2) motivation to do yoga (3) changing experience after doing yoga (4) participant’s expectations. Accorded to the interview, participant’s revealed feeling healthier, and less pain, otherwise participants also felt psychologycally chang to become more confident, calm and positive. Participants hoped to continue to take yoga even when the pain erased and disappeared because they apply it in daily activity and have a better self-awareness. Keywords: experience, musculoskeletal disorders, therapy, yoga